A comparative study of corporate social responsibility and alternative business models on development within disadvantaged communities in South Africa - Naude, Kerry Ann (My University, 2015)
ABSTRACT The influence of corporate social responsibility on development within historically disadvantaged communities has produced average and in some cases, sub-optimal results. With the acknowledgement that existing levels of development within South Africa are insufficient to remedy the challenges experienced in the country, and that sustainable growth may come from the development of the informal business sector, there is a growing recognition that CSR based initiatives could be used more effectively to contribute toward greater levels of development in South Africa. This study explores the critical characteristics of success and failure in business-related CSR initiatives in historically disadvantaged communities. Semi structured interviews were used to gather the views and perspectives of CSR experts, enterprise development experts, CSR executives, CSR managers, informal business owners and community members involved in business-related CSR initiatives. The study uncovered common characteristics for success and failure of business-related CSR initiatives as well as the potential influence that an Alternative Business Model (ABM) approach that is integrated into a business-related CSR initiative can have on informal business sector development.
MBA 2015
Keywords: Social responsibility of business,Community development,Informal sector (Economics)